What Attributed to Abu Hatim Al-Sijistani from a Mistake or Erred in Matters of “Alwaqf Walaibtida’”: Study and Analysis - Sulaimani , Wasim Muhammed (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: The study aims to demonstrate the extent of authors’ interest in Abu Hatim Sijistani’s sayings and explain the reasons that prompted these authors to respond to him. It examines those who replied to him and traced his work, particularly in the science of Alwaqf Walaibtida’, as well as those who defended his statements, interpreted them, and indicated their meaning. Methods: The study adopted an inductive approach to analyzing the critics’ sayings about Abu Hatim. It aims to reveal the most significant reasons that led them to criticize his sayings, rather than those of other authors. Results: The study found that authors often relied on Abu Hatim’s opinion and considered his book, "Al-Maqatea," as a primary source for their works. His sayings were used in various books because of the book’s age and advanced nature. Furthermore, the difference in the grammatical school was a deliberate factor that led some Kufa scholars to respond to him, with al-Anbari being the first to do so. The research also indicated that not all of al-Anbari’s responses to Abu Hatim were correct. Conclusions: The study recommends adhering to the words of scholars and verifying the validity of what is attributed to them. Furthermore, it suggests studying the words of Abu Hatim al-Sijistani and other extensively discussed authors.